2017
DOI: 10.1094/phyto-04-17-0144-r
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Amplification and Lateral-Flow Assay for Detecting Crown-Gall-Causing Agrobacterium spp.

Abstract: Agrobacterium is a genus of soilborne gram-negative bacteria. Members carrying oncogenic plasmids can cause crown gall disease, which has significant economic costs, especially for the orchard and nursery industries. Early and rapid detection of pathogenic Agrobacterium spp. is key to the management of crown gall disease. To this end, we designed oligonucleotide primers and probes to target virD2 for use in a molecular diagnostic tool that relies on isothermal amplification and lateral-flow-based detection. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 34 publications
2
20
0
2
Order By: Relevance
“…Shorter PCR primers (typically between 18 and 25 nucleotides) can also be used in the RPA reaction but may decrease the reaction speed and sensitivity. 42 Application of short PCR primers in RPA has been demonstrated by Mayboroda et al, 43 Martorell et al, 37 Wang et al 44 and Fuller et al 45 The latter two authors have shown that the PCR primers used in RPA resulted higher analytical sensitivity of detection compared to their usage in PCR: RPA detected 100 DNA copies of genetically modified GTS 40-3-2 soybean and 3.5 pg of genomic DNA of Agrobacterium spp. respectively, while the benchmark method PCR detected 1000 DNA copies and 350 pg of genomic DNA respectively.…”
Section: Lateral Flow Stripmentioning
confidence: 99%
See 3 more Smart Citations
“…Shorter PCR primers (typically between 18 and 25 nucleotides) can also be used in the RPA reaction but may decrease the reaction speed and sensitivity. 42 Application of short PCR primers in RPA has been demonstrated by Mayboroda et al, 43 Martorell et al, 37 Wang et al 44 and Fuller et al 45 The latter two authors have shown that the PCR primers used in RPA resulted higher analytical sensitivity of detection compared to their usage in PCR: RPA detected 100 DNA copies of genetically modified GTS 40-3-2 soybean and 3.5 pg of genomic DNA of Agrobacterium spp. respectively, while the benchmark method PCR detected 1000 DNA copies and 350 pg of genomic DNA respectively.…”
Section: Lateral Flow Stripmentioning
confidence: 99%
“…respectively, while the benchmark method PCR detected 1000 DNA copies and 350 pg of genomic DNA respectively. 44,45 The company that sells the commercialised RPA reagents, TwistDx™ Ltd (see section 2.4 and Tables 2 and 3 for more details) provides additional probes that can be incorporated during the RPA reaction. The TwistAmp™ exo probe (typically between 46 and 52 nucleotides) and the TwistAmp® fpg probe (typically between 32 and 35 nucleotides) are used for fluorogenic real-time detection (Fig.…”
Section: Lateral Flow Stripmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of ongoing research, we have evaluated the model of Equation for a real‐time RPA protocol, which uses dual‐labeled (fluorophore/quencher) oligonucleotide probes for generating a fluorescent signal. An RPA‐based assay for Agrobacterium spp . served as the basis for the real‐time protocol; Figure illustrates replicate measurements for a positive Agrobacterium control sample.…”
Section: Discussionmentioning
confidence: 99%